Application of Technical Rationality and Reflective Practice in Managing Intricate Construction Claims: A Case Study in Qatar - , Chandana Jayalath (Archives of Current Research International, 2023)
The propensity towards the increased number of court cases, gaps between theory and practice and the intricacy associated with construction claims tend to pose messy and indeterminate situations where the traditional instrumental approaches are criticised for sub-optimal outcomes. This essentially warrants some kind of a reflection in action merged with technical rationality in making professional judgments. There is little to no literature on how construction practitioners synthesize both paradigms within a single project, reinforcing the apparent divide between them. This study therefore explores the potential of implementing reflective practice into construction claim analysis by using a case study. The project selected was a 12 km bypass in Doha Qatar consisting of a 10-lane section which provided qualitative data related to 19 contractual heads that are recognized as being effectively and amicably settled. The literature shows 17 characteristics of each domain. The study emphasized that two paradigms (technical rationality and reflective practice) are not remote, but concomitant with several discrete relationships. Recommendations were given for construction practitioners to use reflective practice, along with technical rationality to submit sensible claims and frame out solutions for future applications. It is apparent that the use of algorithms, industrial knowhow and thumb rules provide stimuli in claims analysis combining both the paradigms fostering a culture of sensible claims.